2004
DOI: 10.1007/s11182-005-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

Statistical estimates of the contribution of multiply scattered radiation to the intensity of acoustic radiation transmitted through a lower 500-m atmospheric layer

Abstract: 551.596The problem of acoustic radiation propagation through a lower 500-m plane-stratified turbulent atmospheric layer has been solved by the Monte Carlo method. Statistical estimates of the contribution of multiply scattered radiation to the transmitted acoustic radiation intensity are obtained. A point omnidirectional source of monochromatic acoustic radiation was placed at a height of 35 m above the absorbing Earth's surface. Statistical estimates of the contribution of multiply scattered radiation to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The outer scale of turbulence L 0 was set equal to 10, 15, 20, 40, 60, and 80 m. Acoustic radiation of the source propagated through plane-parallel layers of the atmosphere with the coefficients of classical and molecular absorption σ cl (j) and σ mol (j) and scattering on turbulent temperature and wind velocity fluctuations σ T (j) and σ V (j) being constant within these layers, where j = 1, …, 25. Formulas for calculating the corresponding coefficients and compact formulas for the phase functions of sound scattering on the turbulent temperature and wind velocity fluctuations were taken from [8]. In our calculations, the vertical profiles of the air temperature, pressure, and sound speed were taken from the standard model of the atmosphere at middle latitudes in summer [13].…”
Section: Model Of the Atmospherementioning
confidence: 99%
See 1 more Smart Citation
“…The outer scale of turbulence L 0 was set equal to 10, 15, 20, 40, 60, and 80 m. Acoustic radiation of the source propagated through plane-parallel layers of the atmosphere with the coefficients of classical and molecular absorption σ cl (j) and σ mol (j) and scattering on turbulent temperature and wind velocity fluctuations σ T (j) and σ V (j) being constant within these layers, where j = 1, …, 25. Formulas for calculating the corresponding coefficients and compact formulas for the phase functions of sound scattering on the turbulent temperature and wind velocity fluctuations were taken from [8]. In our calculations, the vertical profiles of the air temperature, pressure, and sound speed were taken from the standard model of the atmosphere at middle latitudes in summer [13].…”
Section: Model Of the Atmospherementioning
confidence: 99%
“…In [4] it has been demonstrated that the extinction of vertically propagating sound beams is determined by their broadening due to the atmospheric turbulence. Difficulties of analytical approaches to a solution of the problem of acoustic radiation transfer through the outdoor atmosphere call for the use of numerical methods (for example, see [5,6]), from which the method of statistical simulation (Monte Carlo) is most promising [7][8][9][10][11][12]. This method allows sound scattering on the refractive index fluctuations caused by wind velocity and temperature inhomogeneities to be taken into account for the most realistic models of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The extinction coefficients were equal to the sum of the coefficients of classical and molecular absorption and coefficients of sound scattering by temperature and wind velocity fluctuations. Formulas for calculations of the corresponding coefficients and compact formulas for the normalized phase functions of scattering by turbulent fluctuations of the temperature and wind velocity were presented in [2].…”
Section: Model Of the Mediummentioning
confidence: 99%
“…Random trajectories of particles (phonons) were simulated with the use of both well-known algorithms [6] and algorithms constructed in [1, 2,7,8] with allowance for the specifics of sound interaction with the atmosphere. Details of the computational algorithm were discussed in [1,2].…”
Section: Computational Algorithmmentioning
confidence: 99%
See 1 more Smart Citation